ROLE OF ENVIRONMENTAL ALLERGENS ON ATOPIC DERMATITIS - Wardhana, M. (BALI MEDICAL JOURNAL; Vol 3 No 1 (2014), 2014)
Background: Atopic dermatitis (AD) is a chronic eczematous skin disease that develops in a patient with atopic diathesis, which is characterized by an increased liability to produce IgE antibodies for allergens mostly derived from environmental or inhalant allergens and food allergens. They are produced by cell-mediated allergic contact reactions, and recently contact sensitivity to various environmental allergens has been demonstrated in patients with AD. Atopic patients are recognized by their ability to produce large amounts of specific IgE antibodies to common substances as environmental allergens, i.e. house dust mites, grass pollens, animal danders, molds, food, etc. These antibodies can be detected by skin prick test. The aim of this study was to identify the sensitization against environmental or inhalants allergens through skin prick tests in the patients with atopic dermatitis. Material and Methods: This is a retrospective, descriptive study. We revised all medical records of patients with AD since January 2002 to December 2004 in the Out Patients Unit of Sanglah General Hospital, Bali-Indonesia. The variables studied were: gender, age, work related, diagnosis associates to AD, and prick test of environmental allergens. Results: In 3 years periods we had revised 46 of patients with AD that was done skin prick tests. The median age was 38 years (range 29-54 years), 34/46 (73.9 %) of these were male and 12 (26.1 %) female. Twenty nine patients presented pure AD, and 17 patients had AD with asthma and allergic rhinitis. Only 16 (34.7%) of patients had no history of allergic disease. Thirsty six of 46 (78.20%) of all tested AD patients had a positive skin prick tests against inhalant (aeroallergens) 16 patients and food allergens 21 patients. Sixteen patients with positive of skin test include; dust mite in 12 patients, animal dander in 10 patients, grass pollen in 9 patients and cockroach in 6 patients. Conclusion: We concluded that Environmental work related particularly dust-mite were significant that contributed to symptoms exacerbation and positive skin prick test. The skin prick tests are important methods to determine inhalant allergens in work related that exacerbation of AD patients.
Keywords: Atopic dermatitis, Environmental, allergens, skin prick test.